Cation exchange capacity for soils of drained thaw lake basins near Barrow, Alaska, 2010 ... - Raab, T.K.; Lipson, D.A. (NSF Arctic Data Center, 2013)
Cation exchange capacity (CEC) and porosity-weighted CEC (Qv) for soils of drained thaw lake basins near Barrow, Alaska (AK) representing young, medium, old and ancient age classes. See Lipson et al. (2013) GBC 27:1-11. ...